2008
DOI: 10.1111/j.1558-5646.2008.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

SOCIALLY ACQUIRED HOST‐SPECIFIC MIMICRY AND THE EVOLUTION OF HOST RACES IN HORSFIELD'S BRONZE‐CUCKOOCHALCITES BASALIS

Abstract: Coevolution between parasites and their hosts typically leads to increasing specialization on host species by the parasite. Where multiple hosts are parasitized, specialization on each host can result in genetic divergence within the parasite population to create host races, and, ultimately, new species. We investigate how host-specific traits arise in Horsfield's bronze-cuckoo Chalcites basalis nestlings. Newly hatched cuckoos evict host young from the nest, yet in the absence of a model they accurately mimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
154
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(160 citation statements)
references
References 47 publications
6
154
0
Order By: Relevance
“…Thus, our results provide novel evidence of a further escalation in the coevolutionary arms race between cuckoos and their hosts: the evolution of visual mimicry of host nestlings by cuckoos in response to rejection by hosts. Together with two other recent studies [6,48], this study counters theoretical arguments that in both avian and insect brood-parasitic systems coevolution will not extend beyond the egg stage [16,49]. To date, the only other suggestion that rejection by hosts has selected for mimetic parasitic offspring in any brood-parasitic system comes from recent work on an insect social parasite.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Thus, our results provide novel evidence of a further escalation in the coevolutionary arms race between cuckoos and their hosts: the evolution of visual mimicry of host nestlings by cuckoos in response to rejection by hosts. Together with two other recent studies [6,48], this study counters theoretical arguments that in both avian and insect brood-parasitic systems coevolution will not extend beyond the egg stage [16,49]. To date, the only other suggestion that rejection by hosts has selected for mimetic parasitic offspring in any brood-parasitic system comes from recent work on an insect social parasite.…”
Section: Resultssupporting
confidence: 66%
“…However, our results here reveal that the two cuckoo species are equally similar to superb fairy-wren chicks in skin colour ( figure 4d,g). Additional cues used by superb fairy-wrens to discriminate shining bronze-cuckoos may include rictal flange colour, which does not resemble that of fairy-wrens (figure 4f,i ), and nestling begging calls [6,11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10: 20140046 which increased call similarity after hatching, and hence-as we previously showed-increased detectability of an intruder cuckoo chick after hatching. Assuming that cuckoo embryos could learn (for which there is no evidence to date [5]), increased female incubation call rate (which begins late in the incubation phase [4]) would have a lesser effect on cuckoo embryos that hatch days earlier than host embryos (early cuckoo hatching is favoured to evict host eggs). This study provides a mechanistic explanation for how 'experience' with a brood parasite near the territory can lead to increased cuckoo abandonment [19], which is a pattern found across numerous studies [6].…”
Section: Discussionmentioning
confidence: 99%
“…In our long-term research, we found that Superb Fairywren females called to their eggs and vocally tutored their embryos a particular element of their incubation call during incubation, which was later produced by the nestlings as a begging call (ColombelliNégrel et al 2012). Better-imitated maternal call elements by nestlings elicited more food provisioning from parents and revealed the presence of foreign chicks, including interspecific brood parasite nestlings that did not learn as embryos (Langmore et al 2008, Colombelli-Négrel et al 2012. Females with higher incubation call rate produced offspring with higher begging call similarity and females increased their incubation call rate when there were more parasitic Horsfield's Bronze-cuckoos (Chalcites basalis) in the area (Colombelli-Négrel et al 2012, Kleindorfer et al 2014b).…”
Section: Introductionmentioning
confidence: 99%